Message in a bottle [compact disc, unabridged] - Sparks, Nicholas (Hachette Audio, 2015)
Divorced and disillusioned about relationships, Theresa is jogging when she finds a bottle on the beach. Inside is a letter of love and longing to 'Catherine,' signed simply 'Garrett.' Challenged by the mystery and pulled by emotions she doesn't fully understand, Theresa begins a search for this man that will change her life. What happens to her is unexpected, perhaps miraculous-an encounter that embraces all our hopes for finding someone special.